2005
DOI: 10.1097/01.ju.0000143194.79287.a9
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis and Chemotherapy for Bladder Cancer

Abstract: Much current research in bladder cancer is aimed at restoring chemosensitivity by shifting the cell toward a pro-apoptotic phenotype. Successful translation of this work into clinical practice may improve survival in patients in whom prognosis is currently poor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 63 publications
1
39
0
1
Order By: Relevance
“…Inducing apoptosis is an important strategy to overcome cancer [36,37,38]. Previous studies proved that activations of caspase-9 and caspase-3 lead to apoptosis in FaDu cells [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Inducing apoptosis is an important strategy to overcome cancer [36,37,38]. Previous studies proved that activations of caspase-9 and caspase-3 lead to apoptosis in FaDu cells [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…27,28 Apoptosis (programmed cell death) results from a cascade of intrinsic and extrinsic signals and depends on the balance between pro-and anti-apoptotic proteins. 34 Caspase-3 is a pro-apoptotic enzyme that has been associated with higher pathologic grade, stage and presence of lymph node metastasis in radical cystectomy specimens. 29 In a study using multiple apoptosis markers to assess their value in improving the accuracy of predicting outcomes for patients with UC, Karam and colleagues demonstrated that loss of caspase-3 was an independent predictor of bladder cancerspecific survival after radical cystectomy.…”
Section: Biomarkers Of Prognosis and Therapeutic Efficacymentioning
confidence: 99%
“…2 Bladder cancer has been shown to resist programmed cell death both with altered expression of pro-and antiapoptotic proteins. [3][4][5] Survivin is a member of the inhibitor of apoptosis (IAP) gene family that has been found to control mitotic progression and induces changes in gene expression that are associated with tumor cell invasiveness. 6,7 Survivin mRNA is selectively expressed during embryonic and fetal development, 8 becomes undetectable or expressed at low levels in most differentiated normal adult tissues, and is overexpressed in human cancers.…”
mentioning
confidence: 99%